Tumor-associated macrophages in Human breast, colorectal, lung, ovarian and prostate cancers - Larionova, Irina V.; Tuguzbaeva, Gulnara; Ponomaryova, Anastasia; Stakheyeva, Marina; Cherdyntseva, Nadezhda; Pavlov, Valentin; Choinzonov, Evgeniy; Kzhyshkowska, Julia (Frontiers in oncology, 2020)
Tumor-associated macrophages (TAMs) are major innate immune cells that constitute up to 50% of the cell mass of human tumors. TAMs are highly heterogeneous cells that originate from resident tissue-specific macrophages and from newly recruited monocytes. TAMs’ variability strongly depends on cancer type, stage, and intratumor heterogeneity. Majority of TAMs are programmed by tumor microenvironment to support primary tumor growth and metastatic spread. However, TAMs can also restrict tumor growth and metastasis. In this review, we summarized the knowledge about the role of TAMs in tumor growth, metastasis and in the response to cancer therapy in patients with five aggressive types of cancer: breast, colorectal, lung, ovarian, and prostate cancers that are frequently metastasize into distant organs resulting in high mortality of the patients. Two major TAM parameters are applied for the evaluation of TAM correlation with the cancer progression: total amount of TAMs and specific phenotype of TAMs identified by functional biomarkers. We summarized the data generated in the wide range of international patient cohorts on the correlation of TAMs with clinical and pathological parameters of tumor progression including lymphatic and hematogenous metastasis, recurrence, survival, therapy efficiency. We described currently available biomarkers for TAMs that can be measured in patients’ samples (tumor tissue and blood). CD68 is the major biomarker for the quantification of total TAM amounts, while transmembrane receptors (stabilin-1, CD163, CD206, CD204, MARCO) and secreted chitinase-like proteins (YKL-39, YKL-40) are used as biomarkers for the functional TAM polarization. We also considered that specific role of TAMs in tumor progression can depend on the localization in the intratumoral compartments. We have made the conclusion for the role of TAMs in primary tumor growth, metastasis, and therapy sensitivity for breast, colorectal, lung, ovarian, and prostate cancers. In contrast to other cancer types, majority of clinical studies indicate that TAMs in colorectal cancer have protective role for the patient and interfere with primary tumor growth and metastasis. The accumulated data are essential for using TAMs as biomarkers and therapeutic targets to develop cancer-specific immunotherapy and to design efficient combinations of traditional therapy and new immunomodulatory approaches.
Gesehen am 21.08.2024